Modeling and Formal Verification of a Passive Optical Network on Chip Behavior - Gheorghe Iugan, Luiza; Nicolescu, Gabriela; O’Connor, Ian (Electronic Communications of the EASST, 2009)
Many of the modern Systems-on-Chip integrate a high density of heterogeneous components such as different processors, a wide range of hardware components, as well as complex interconnects that use different communication protocols. On-chip physical interconnections represent a limiting factor for the performance and energy consumption. Currently, the optical interconnects integrated on chip are a viable alternative for on chip interconnects. However, the access to physical prototyping of these interconnects is a major challenge because this systems require very recent technologies, still difficult to access. Thus, their high-level modeling and validation are mandatory. This paper proposes the modeling and the formal verification for the global validation of the behavior of a passive integrated photonic routing structure using models that are based on timed automata.